1969
DOI: 10.1111/j.1423-0410.1969.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Clearance of Rh Positive Blood During Experimental Rh Immunisation

Abstract: Summary. When Rh negative male volunteers were given successive small injections of Rh positive blood, it was repeatedly found that rapid clearance of the cells took place in the absence of detectable antibody. It is thought likely that primary immunisation to the D (Rho) antigen had occurred in these cases and that a similar state occurs as a result of Rh positive pregnancies in Rh negative mothers. These findings have a relevance to the assessment of trials in which gammaglobulin anti‐D is given to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…The observations of Woodrow et al (1969), supported by those reported here, strongly suggest the existence of two kinds of Rh negative subject, one who is capable of becoming immunized to the Rh antigen and does so after a single stimulus, and one who cannot become immunized to Rh, even after repeated stimuli. Of course, the difference may not be absolute and it may be that one kind becomes immunized much more easily than the other.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observations of Woodrow et al (1969), supported by those reported here, strongly suggest the existence of two kinds of Rh negative subject, one who is capable of becoming immunized to the Rh antigen and does so after a single stimulus, and one who cannot become immunized to Rh, even after repeated stimuli. Of course, the difference may not be absolute and it may be that one kind becomes immunized much more easily than the other.…”
Section: Discussionsupporting
confidence: 83%
“…The results of Woodrow et al(1969), of which a preliminary report was given by Krevans et aE (1964, were essentially similar: 11 Rh negative subjects were given 3-11 injections of 5 ml (occasionally 10 ml) of Rh-positive blood at intervals usually of 6 weeks but occasionally as long as 7 mth. Four out of 11 of the subjects failed to develop anti-Rh(D) and in these the Cr survival of Rh positive red cells was normal on three to five occasions.…”
Section: Discussionmentioning
confidence: 78%
“…3 and 6 -would seem to have similar antibody response to those described by Gunson et al [3] and by Mollison et al [5], who had volunteers with anti bodies which decreased in titre or disappeared after repeated stimuli. This would appear to be similar to the type of response reported by Woodrow et al [6], where the survival time of Rh (D)-positive cells injected into Rh (D)-negative volunteers increased, despite second and third injections which lead eventually to detectable antibody formation: It may represent a change from the production of IgM to IgG anti-D.…”
Section: Discussionsupporting
confidence: 65%
“…Although IgM development during a primary exposure to antigen can actually shorten the lifespan of transfused blood [101, 102], primary antibody responses do not typically result in a routinely detectable HTR. However, during this primary antigen exposure, T cell-mediated class switching results in significant production of IgG.…”
Section: Factors Influencing Complement Activationmentioning
confidence: 99%